Karakteristik dan kualitas semen sapi Sumba Ongole dalam pengencer tris yang disuplementasi dengan susu skim pada suhu 3-5 ºC - Fiktor Ngguli Hunggu Mila; Alexander Kaka; Yessy Tamu Ina (Universitas Sulawesi Barat, 2021)
The aims of this study were to determine the characteristics and quality of fresh semen from Sumba Ongole (SO) bulls which were diluted with tris dilution supplemented with skim milk. The study used a completely randomized design consisting of 4 treatments and 5 replications. The treatments were P0 = 100 % Tris, P1 = 88 % Tris + 12 % Susu skim, P2 = 86 % Tris + 14 % Susu skim, dan P3 = 84 % Tris + 16 % Susu skim. The parameters observed were the colour, smell, consistency, pH, volume, motility, viability, and abnormalities of semen. The results showed that the characteristics of the semen were normal, the color of the semen was creamy white, the semen volume was 4.6 ml, the consistency was moderate, pH 6.3, the smell was typical of SO cattle, the motility was 80%, the mass movement was +++, the concentration was 758 million/ ml, viability is 74.24% and abnormality is 16.12%. The characteristics and quality of cement in the four treatments showed no significant difference (P>0.01). The motility and viability of spermatozoa in each treatment were able to survive up to day 3. The Tris diluent with the addition of skim milk was not able to maintain the characteristics and quality of the semen.